Litterfall yield in a tract of terra firme forest adjacent to a mangrove stand on the Ajuruteua peninsula, Bragança, Pará - Nascimento, Raquel do Espírito Santo Aguiar do; Mehlig, Ulf; Abreu, Maria Milena de Oliveira; Menezes, Moirah Paula Machado de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The present study focusses on differences in litter production of a terra firme forest fragment and an adjacent mangrove stand on the coast of the Bragança region. Litterfall was quantified by means of 10 litter traps (0.5 m2) in the mangrove and 10 in terra firme forest, installed along a transect orthogonal to the division between the two ecosystems. Material was collected fortnightly. Litter production in the mangrove forest (11.8 t·ha-1yr-1) was by a third higher than in terra firme forest (8.7 t·ha-1yr-1). Leaves were the most important litter component in both ecosystems (68 e 63% for mangrove and terra firme, respectively). In the mangrove, Rhizophora mangle contributed the major part of litter material. In terra firme, leaves of species of the families Simaroubaceae, Burseraceae e Arecaceae contributed 13, 12 e 11% of the leaf total; 54% of leaves were not identified taxonomically. In the mangrove, reproductive litter components showed seasonal patterns. It was not possible to identify a clear seasonal pattern in R. mangle leaf litter fall. However, in mangrove and terra firme, total litter production was higher in dry season.
Keywords: Arecaceae; Burseraceae; Simaroubaceae; Rhizophora mangle; Phenology; Ash content